2021
DOI: 10.1007/s11071-021-06894-2
|View full text |Cite
|
Sign up to set email alerts
|

The “backward-looking” effect in the continuum model considering a new backward equilibrium velocity function

Abstract: The "backward looking" effect in the continuum model considering a new backward equilibrium velocity function. AuthorsMd. Anowar Hossain a) , Jun Tanimoto a), b) a

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Zhai and Wu [58] considered the traffic interruption probability in the OV model and proposed a developed continuum traffic flow model, the results showed that the improved model can enhance the stability of traffic flow. In this context, an extensive literature has developed on the extended versions considering new characteristics, such as multiple OV with different probabilities [59], backwards-looking [60], bi-directional information [61], the bifurcation phenomena [62], slope and curved road [63,64],vehicles' taillight [65], and feedback control [66].…”
Section: Macroscopic Traffic Flow Modelsmentioning
confidence: 99%
“…Zhai and Wu [58] considered the traffic interruption probability in the OV model and proposed a developed continuum traffic flow model, the results showed that the improved model can enhance the stability of traffic flow. In this context, an extensive literature has developed on the extended versions considering new characteristics, such as multiple OV with different probabilities [59], backwards-looking [60], bi-directional information [61], the bifurcation phenomena [62], slope and curved road [63,64],vehicles' taillight [65], and feedback control [66].…”
Section: Macroscopic Traffic Flow Modelsmentioning
confidence: 99%
“…However, transport facilities face numerous issues, including limited resources and poor management. Therefore, several traffic models have been developed based on theories and experiments, including microscopic models [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ], macroscopic models [ [8] , [9] , [10] , [11] , [12] , [13] ], lattice hydrodynamical models [ [14] , [15] , [16] , [17] , [18] ], and cellular automaton (CA) models [ [19] , [20] , [21] , [22] , [23] , [24] ]. Most of these models have been validated under an ideal traffic flow environment with homogeneous vehicle sizes and capabilities, which could not ensure an actual traffic flow field.…”
Section: Introductionmentioning
confidence: 99%
“…These models can commonly be categorized into two distinct types [ 1 ]. The first type is known as the macroscopic or continuum model, which likens traffic flow to a compressible fluid and is investigated using fluid dynamics principles [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Conversely, the second type is the microscopic or ultra-discrete model, which delves into the interactions between individual vehicles as well as their relationship with the road infrastructure [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%